Aplikasi Augmented Reality Penuntun Shalat Untuk Anak Usia Dini - Ramdan Adjis; Vivi Pegie Rantung; Sondy Kumajas; Gladly Caren Rorimpandey (JOINTER : Journal of Informatics Engineering, 2021)
Abstract— This prayer guide Augmented Reality application is designed for early childhood with parental supervision. The purpose of developing this application is to give new experiences for early childhood in learning prayer with technology of Augmented Reality Application. The method used is Multimedia Development Life Cycle (MDLC) wich consists of six stages, namely Concept, Design, Material Collection, Assembly, Testing, and Distribution. After the application development process, the result of this research is anAugmented Reality Application that is used by early childhood in learning prayer using a Smartphone.